Verryking as 'n leksikografiese prosedure - Gouws, Rufus H (Stellenbosch Papers in Linguistics Plus, 2011)
In metalexicography the term "enriched item" refers to a dictionary item of which the centre has been expanded, i.e. enriched, by other item parts so that a new complex item is established as topic. This paper provides a brief discussion of the prevailing notion of enrichment. It is then indicated that the lexicographic practice has already increased the scope of this procedure, albeit that these innovations have not yet sufficiently been described in metalexicographic work. The lack of a theoretical discussion often leads to a haphazard application of enrichment where this procedure is not optimally employed. A classification is given of different procedures of enrichment, allowing a distinction between data-homogeneous and data-heterogeneous enrichment. These procedures can present examples of either single or double enrichment. It is shown that enrichment does not only target a single item but also an article zone where the procedure of enrichment can add another item, representing either the same or a different data type, to complement the original item. A typological distinction is made between enrichment aimed at expanding the data transfer in a dictionary article, enrichment aimed at enhancing the access in a dictionary and enrichment aimed at adding to the lexicographic functions. This last type is discussed with reference to the addition of the cognitive function in a dictionary with communication as primary function. The paper argues in favour of an even closer relation between lexicographic theory and practice, which will lead to a better description of enrichment but also a better application of this lexicographic procedure.